2005
DOI: 10.1063/1.1865313
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and texture dependence of the dielectric anomalies and dc conductivity of Bi3TiNbO9 ferroelectric ceramics

Abstract: Ceramics of composition Bi 3 TiNbO 9 ͑BTN͒ and perovskite-layered structure ͑Aurivillius type͒ ͓B. Aurivillius, Ark. Kemi 1, 463 ͑1949͔͒ were processed by natural sintering and hot pressing from amorphous precursors. Precursors were obtained by mechanochemical activation of stoichiometric mixtures of oxides. These materials are in general interesting for their use as high-temperature piezoelectrics. Among them, BTN possesses the highest ferroparaelectric phase-transition temperature ͑Ͼ900°C͒. The transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…The resistivity of BTNO is only about 10 7 Ω·cm below 400°C, 9 for example. Most of the studies reported on BTNO have concentrated on the crystal structure, 3,8,10,11 synthesis, and electrical properties of pure bulk BTNO ceramics, 12–15 Other studies have focused on the properties of intergrowth compounds such as (Bi 3 TiNbO 9 ) x (SrBi 2 Nb 2 O 9 ) 1− x 16 and (Bi 3 TiNbO 9 ) x (Bi 4 Ti 3 O 12 ) 1− x 17 . Only a few works have addressed the properties of cation‐modified BTNO‐based ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…The resistivity of BTNO is only about 10 7 Ω·cm below 400°C, 9 for example. Most of the studies reported on BTNO have concentrated on the crystal structure, 3,8,10,11 synthesis, and electrical properties of pure bulk BTNO ceramics, 12–15 Other studies have focused on the properties of intergrowth compounds such as (Bi 3 TiNbO 9 ) x (SrBi 2 Nb 2 O 9 ) 1− x 16 and (Bi 3 TiNbO 9 ) x (Bi 4 Ti 3 O 12 ) 1− x 17 . Only a few works have addressed the properties of cation‐modified BTNO‐based ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the piezoelectric properties, A and B site modification are commonly used [5][6][7][8]. Texturing technologies, such as hot-forging [9], hot-pressing [10], spark plasma sintering (SPS) [11] and tape casting [12] is another way to improve the piezoelectric properties of Aurivillius type ceramics. CaBi 4 Ti 4 O 15 (CBT) is a member of Aurivillius family with high Curie temperature (T c = 790 8C) and low dielectric loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lower piezoelectric coefficient (d 33 ) which is restricted by the two-dimensional rotation of the polarization orientation and the high coercive fields (E c ) has greatly restricted their applications. [5][6][7][8][9][10] Bismuth titanate niobate (Bi 3 TiNbO 9 , NBT), a member belonging to the BLSFs, possessing a very high T C (~913°C), is deemed as one of the rare candidates that can be utilized at temperatures above 600°C. However, similar to other BLSFs ceramics, the pristine NBT exhibits a very low d 33 (<7 pC/N) and relatively low resistivity (6.90 × 10 4 Ω•cm at 600°C).…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to other BLSFs ceramics, the pristine NBT exhibits a very low d 33 (<7 pC/N) and relatively low resistivity (6.90 × 10 4 Ω•cm at 600°C). 9,10 Great efforts need to be paid to realize its practical application.…”
Section: Introductionmentioning
confidence: 99%